Wrasses of the Galápagos Islands, with the description of a new deepwater species of Halichoeres (Perciformes: Labridae) - Baldwin, Carole C.; McCosker, John E. (Revista de Biología Tropical, 2001)
Halichoeres raisneri, new species, is described from three specimens captured by the Johnson Sea Link submersible at 114-125 m off Wolf Island, Galápagos. Distinctive features of the new species include a dorsally projecting fleshy flap along the posterior three-quarters of the upper lip and the absence of a canine tooth at the corner of the upper jaw. The body color of freshly caught females is pale pink with two yellow stripes and five prominent pink spots above the uppermost stripe. Similarities between the new species and other labrids are discussed, and a key to the 16 nominal species of Labridae known from the Galápagos Islands is provided. Decodon melasma is recorded from the Archipelago for the first time.